(untitled) (IAHS Medical Journal, 2024)
Background: The prevalence of vitiligo has been reported to range from 0.1% to 8% worldwide. It has a low mortality rate but a high morbidity cost because of its psychological and social effects. Type-1 diabetes mellitus, autoimmune thyroid disease and other autoimmune illnesses have been linked to this condition. This study was performed to assess the occurence of vitiligo among males and females and the epidemiological status of vitiligo in a tertiary Hospital of Dhaka, Bangladesh. Materials and methods: A cross-sectional survey was conducted among 3,212 adults (1,429 males and 1,783 females) in a community of Dhaka between October 2022 and May 2023 at OPD of Delta Medical College. Face-to face interviews were conducted at the OPD of Delta Medical College for each participant and all respondents had their skin examined by dermatologists. The risks of comorbidities associated with vitiligo were evaluated. Results: In this particular research project, most vitiligo patients were between the ages of 13 and 60 years. According to this research, the average age of vitiligo patients was 35.5 years. Here, the proportion rate for this is 2.74%. The ratio of male participants to female participants in this research was M:F = 1:1.51. Only 88 out of the 24 cases were stable, whereas around 64 were unstable. The focused kind of vitiligo was shown to be the most prevalent form of the condition in this particular research. Conclusion: Vitiligo was most common among individuals in Dhaka in their middle 30s and the incidence of the condition rise with age. In adult patients, vitiligo was connected with higher risks of alopecia areata, hypothyroidism, diabetes mellitus and atopic dermatitis. IAHS Medical Journal Vol 7(1), June 2024; 17-21